mCherry contains a fluorescent protein isoform that interferes with its reporter function - Fages-Lartaud, Maxime; Tietze, Lisa; Elie, Florence; Lale, Rahmi; Hohmann-Marriott, Martin Frank (Frontiers in Bioengineering and Biotechnology, 2022)
Fluorescent proteins are essential reporters in cell biology and molecular biology. Here, we reveal that red-fluorescent proteins possess an alternative translation initiation site that produces a short functional protein isoform. The short isoform creates significant background fluorescence that biases the outcome of expression studies. Our investigation identifies the short protein isoform, traces its origin, and determines the extent of the issue within the family of red fluorescent protein. Our analysis shows that the short isoform defect of the red fluorescent protein family may affect the interpretation of many published studies. Finally, we provide a re-engineered mCherry variant that lacks background expression as an improved tool for imaging and protein expression studies.